Discourse Markers of Humor Analysis in Trevor Noah’s Stand-Up Comedy - Zainur Rofiq; Eko Suci Priyono (English Department, Faculty of Humanities, Udayana University, 2021)
Discourse markers have been widely studied in various discourses such as political discourse, legal, media discourse, and even daily conversation. However, there is still a lack of discourse markers research in humor studies. This study was projected to identify the linguistic aspects of humor genre utterances in stand-up comedy performed by Trevor Noah as one of the most influential stand-up comedians. In addition, those linguistic aspect is discourse markers. The data were taken from Trevor Noah’s Video entitle